Ensuring quality open and online learning (eQOOL) [electronic resource] - MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; Skills Commons; The California State University; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 2020)
Quoted from the homepage: Open Education Practices and Quality Assurance of Online Instruction: Institutional practices to assure the quality of online instruction is of critical importance. Design rubrics, professional development programs, examples of quality online course designs can all support faculty's efforts to design and deliver quality online instruction. ePortfolios and Quality Assurance: Openly sharing quality assurance (QA) practices adopted by institutions (including program design, implementation, and assessments) can enable scaling exemplary practices within the faculty community and across campuses. Capturing these practices in open institutional ePortfolios can be an effective means for communicating and collaborating on adopting openly licensed QA evaluation instruments and processes which are included in this website. The MERLOT and SkillsCommons quality assurance program for online instruction, Ensuring Quality Open and Online Learning (eQOOL) is a Creative Commons adaptation of the California State University, Quality Learning and Teaching evaluation instrument that was developed in 2011 (and updated in 2017) after review of related research and careful consideration of existing models for assessing effective online teaching and learning. Explore about 20 open institutional ePortfolios about their QA strategies and the open eQOOL instruments, professional development resources, and examplars.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Electronic portfolios. .; College teaching -- Aids and devices -- Electronic portfolios. .; Universities and colleges -- Curricula -- Aids and devices -- Electronic portfolios. .; Quality assurance -- United States -- Aids and devices -- Virtual; Education, Higher -- United States -- Aids and devices -- Virtual; Universities and colleges -- United States -- Ratings and rankings -- Aids and devices -- Virtual; Quality assurance -- Education, Higher -- United States -- Aids and devices -- Virtual